Financial wellness and quality of life among young employees / Siti Nasuha Aripin and Fadilah Puteh - Aripin, Siti Nasuha; Puteh, Fadilah (Universiti Teknologi MARA, Shah Alam, 2017)
This paper presents a study on financial wellness and quality of life (QoL) among young employees. Report by Bank Negara Malaysia revealed that non-performing loans, credit card debts and bankruptcies among young people in Malaysia have increased significantly. Young employees are facing financial pressures and this has affected their QoL. This study also evaluates the relationship between financial wellness components namely financial satisfaction, financial behavior, and subjective perception and QoL. Data was collected through questionnaire to 260 among young employees in Majlis Perbandaran Klang (MPK). The findings of this study revealed that the mean levels financial wellness variables namely financial satisfaction, financial behavior and subjective perception are 5.50, 5.90 and 6.08 respectively. Meanwhile, reported mean value for QoL was 7.16. The results also depicted that financial satisfaction, r=0.29,p<0.001, financial behavior, r=0.342,p<0.001 and subjective perception, r=0.235,p<0.001) have significant relationship with QoL. Results also found that subjective perception was the most significant predictor of QoL (B=0.257 at p<0.05). Recommendation and suggestions for future research are also discussed.